2013
DOI: 10.1097/sla.0b013e318262a6a6
|View full text |Cite
|
Sign up to set email alerts
|

Murine Gut Microbiota and Transcriptome Are Diet Dependent

Abstract: FF shifted gut microbiota and structural integrity, oxidative stress, and immune function genes, presumably increasing vulnerability to disease in FF mice. Interrogation of microbial and host gene expression in FF neonates may offer new insight on how diet affects disease pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…[32][33][34] The role of immune mechanisms in the regulation of the microbiota has only recently become the subject of investigation. In this study, we identified an IgA-dependent mechanism responsible for the establishment of the "mature" microbiota in adult mice.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34] The role of immune mechanisms in the regulation of the microbiota has only recently become the subject of investigation. In this study, we identified an IgA-dependent mechanism responsible for the establishment of the "mature" microbiota in adult mice.…”
Section: Discussionmentioning
confidence: 99%
“…In hospitals, Serratia species tend to colonize the respiratory and urinary tracts causing nosocomial infections [62, 63]. In related studies of the GI tract, Serratia increased in formula-fed mice [64] and was positively correlated with infants with colic [65]. …”
Section: Discussionmentioning
confidence: 99%
“…We note that diet has been shown to alter microbiota composition and heme oxygenase 1 expression in infants 24 and, more specifically, that oligosaccharides have been found to induce heme oxygenase-1 expression in macrophages and inhibit inflammation in a murine colitis model. 25 We speculate that dietary changes can in fact influence microbiota urobilin production, though further work is needed in this area.…”
Section: Discussionmentioning
confidence: 99%